Metabolic ecology a scaling approach - Sibly, R. M.; Brown, James H. 1942 Sept. 25-; Kodric-Brown, Astrid (Wiley-Blackwell, 2012)
"Most of ecology is about metabolism: the ways that organisms use energy and materials. The energy requirements of individuals - their metabolic rates - vary predictably with their body size and temperature. Ecological interactions are exchanges of energy and materials between organisms and their environments. So metabolic rate affects ecological processes at all levels: individuals, populations, communities and ecosystems. Each chapter focuses on a different process, level of organization, or kind of organism. It lays a conceptual foundation and presents empirical examples. Together, the chapters provide an integrated framework that holds the promise for a unified theory of ecology.The book is intended to be accessible to upper-level undergraduate, and graduate students, but also of interest to senior scientists. Its easy-to-read chapters and clear illustrations can be used in lecture and seminar courses. Together they make for an authoritative treatment that will inspire future generations to study metabolic ecology"--Provided by publisher.